High aspartate transaminase/alanine transaminase ratio predicts poor prognosis in patients with localized upper tract urothelial cancer: a propensity score-matched study in a large Chinese center - Li, Yifan (Onco Targets Ther, 2019)
Purpose: The aim of this study was to evaluate the prognostic value of the aspartate transaminase/alanine transaminase (AST/ALT) ratio in a large Chinese cohort surgically treated for localized upper tract urothelial carcinoma (UTUC) using propensity score matching (PSM) analysis. Methods: Data of 908 consecutive patients with localized UTUC who underwent radical nephroureterectomy (RNU) were retrospectively evaluated. The endpoints of prognosis were progression-free survival (PFS), cancer-speciﬁc survival (CSS) and overall survival (OS) after RNU. We compared these endpoints according to the AST/ALT ratio before and after 1:1 PSM. The independent predictors for PFS, CSS and OS were also analyzed. Results: A high AST/ALT ratio was correlated with unfavorable factors, including elderly age, female gender, history of coronary disease, alcohol and tobacco consumption, lower body mass index, and larger tumor volume. Before PSM, the Kaplan–Meier curves showed signiﬁcantly poorer survival outcomes in PFS, CSS, and OS (all P<0.001) for patients with high AST/ALT ratios. After PSM, the high AST/ALT ratio group also had signiﬁcantly inferior survival outcomes in terms of PFS, OS and CSS (all P<0.001). Furthermore, multivariate analyses revealed that the AST/ALT ratio was an independent predictor for PFS, CSS and OS before PSM (PFS hazard ratio [HR] 1.454, P=0.001; CSS HR 2.577, P<0.001; OS HR 1.925, P<0.001) and after PSM (PFS HR 1.711, P<0.001; CSS HR 2.588, P<0.001; OS HR 1.957, P<0.001). Conclusion: The preoperative AST/ALT ratio can be a convenient and useful prognostic biomarker for patients with localized UTUC.